2023
DOI: 10.1007/s11195-023-09776-0
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sexual Counseling Based on EX‑PLISSIT Model on Improving the Sexual Function of Married Women with Systemic Lupus Erythematosus: A Randomized Controlled Trial

Abstract: Systemic Lupus erythematosus (SLE) is a multisystem autoimmune disease. This disease triggers sexual dysfunction due to physiological, cognitive and mental effects. Since sexual function is often ignored in these patients, this study aimed to investigate the effect of sexual counseling based on EX‑PLISSIT model on improving the sexual function of married women with SLE. This clinical trial was conducted on 101 married women suffering from SLE (18–49 years) residing in Tehran. Randomization was performed by ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It was seen in the literature that other studies based on the Ex-PLISSIT model were conducted in different sample groups such as Multiple Sclerosis, Systemic Lupus Erythematosus and postpartum women. In these studies, it was determined that counseling was effective in improving sexual function (29)(30)(31)(32)(33). It is thought that the randomized controlled studies and the shorter measurement intervals compared to our study may have an effect on the results.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…It was seen in the literature that other studies based on the Ex-PLISSIT model were conducted in different sample groups such as Multiple Sclerosis, Systemic Lupus Erythematosus and postpartum women. In these studies, it was determined that counseling was effective in improving sexual function (29)(30)(31)(32)(33). It is thought that the randomized controlled studies and the shorter measurement intervals compared to our study may have an effect on the results.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, the low education level of the spouses negatively affected the sexual attitudes of the pregnant women (5). In support of this, lack of knowledge is emphasized as the most important factor in the emergence of sexual problems (33). For this reason, there is a need for training and counseling programs to create positive attitudes and raise awareness about sexuality during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assessed the full text of 199 potentially relevant records, and finally included 102 studies. Of these, forty were categorized as studies on mental health [ 21 60 ], and thirty-nine as studies on physical activity and exercise [ 61 99 ]. Fifteen articles studied the effects of diet and nutrition [ 100 114 ], whereas seven studies examined the reduction of harmful exposures [ 115 121 ].…”
Section: Resultsmentioning
confidence: 99%
“…One of these RCTs evaluated disease activity, and did not find that the intervention (biofeedback-assisted CBT) had any effect [ 24 ]. The other two RCTs showed that counseling may have a positive effect on anxiety [ 59 ] and sexual function [ 60 ], respectively. Table 1 shows the included studies of LoE 1 and 2.…”
Section: Resultsmentioning
confidence: 99%